Relación entre la educación socioemocional y el desempeño académico de los estudiantes de educación secundaria de la I.E.P.S.M. N° 60080 Carlos Patricio Olórtegui Sáenz, provincia de Ramón Castilla 2024 - Flores Ramirez, Jhon Lennon (2025)
The present research focuses on the significant relationship between socioemotional education and the academic performance of secondary school students at I.E.P.S.M. N° 60080 Carlos Patricio Olórtegui Sáenz, Mariscal Ramón Castilla Province, in 2024. Specific objectives were established to examine the relationship between aspects of socioemotional education (social skills, classroom climate, values) and academic performance. The study employed a descriptive correlational methodology, using a survey to collect data on each dimension of social-emotional education. The questionnaires included 16 questions for each dimension, administered to students at the institution. The findings show that 44.4% show a good level of social-emotional education; for the academic performance variable, 44.0% gave an outstanding result. In addition, Spearman's Rho test showed a significance of 0.000, which indicates that there is a significant relationship between socioemotional education and the academic performance of secondary school students at I.E.P.S.M. N° 60080 Carlos Patricio Olórtegui Sáenz, Mariscal Ramón Castilla Province, 2024. Likewise, the dimensions social skills, classroom climate and the dimension values show a significance of 0.000, these dimensions are significantly related to the variable Academic Performance.